Contribution of Regional Power Pools for Energy Security in Africa: Empirical Evidence from the Eastern and Southern African Regions - Tefera, Zerubabel G.; Nzomo, Maria (Richtmann Publishing, 2021)
Despite the considerable energy problem in Africa, it is not clear how the proliferation of regional power pool (RPPs), as the most feasible solution, address the problem by fostering energy cooperation. The main research objective was to analyse and compare the role of RPPs, particularly the Eastern and Southern African power pools (EAPP and SAPP), in fostering energy cooperation and addressing energy security in their respective sub-regions. The study employed a mixed research design. The study targeted 100 leaders and senior experts from the EAPP, SAPP, regional economic communities, financial institutions, scholars, the African Union (AU), and the United Nations. Qualitative data were analysed thematically, while quantitative data was analysed via descriptive and inferential analysis. Simple linear regression models were used to test the hypotheses. From the finding, in Eastern Africa, weak power pool arrangement, EAPP, has contributed significantly to the prevailing energy insecurity ( =.345, p<.05); on the other hand, strong regional power pool in Southern Africa, SAPP, significantly contributes to energy security ( =.323, p< .05), thus depicting that strong RPP is a key predictor of energy security in the region. Based on the findings, the study concludes that the institutionalised attempt to energy security in Africa can address most of Africa’s energy security challenges. However, Africa must embrace the role of these energy security institutions by pursuing a deliberate policy to strengthen them so that its overall integration project, as stipulated in the African Union Agenda 2063, can be materialised. Received: 12 August 2021 / Accepted: 13 October 2021 / Published: 5 November 2021